A Refined Approach for Angle of Attack Estimation and Dynamic Force Hysteresis in H-Type Darrieus Wind Turbines - Jan Michna; Krzysztof Rogowski (Energies)
This study investigates the aerodynamic performance and flow dynamics of an H-type Darrieus vertical axis wind turbine (VAWT) using combined numerical and experimental methods. The analysis examines the effects of operational parameters, such as rotor solidity and pitch angle, on aerodynamic loads and flow characteristics, using a 2-D URANS simulation with the Transition SST model to capture transient effects. Validation was conducted in a low-turbulence wind tunnel to observe the impact of variable flow conditions. The LineAverage method for determining the angle of attack demonstrated strong correlations between rotor configuration and load variations, particularly highlighting the influence of blade number and pitch angle on aerodynamic efficiency. This research supports optimization strategies for Darrieus VAWTs in urban environments, where turbulent, low-speed conditions challenge conventional wind turbine designs.